Protected remnants of calcareous grasslands bridge the gap in the distribution of a habitat specialist insect – a case of Cicadetta cantilatrix Sueur et Puissant, 2007 in the area of Polish Uplands - Bobrek, Rafał; Kusal, Katarzyna; Kusal, Bartłomiej (Ecological Questions, 2026)
Since the recent application of bioacoustic methods in the research of taxa forming a species complex of mountain cicada Cicadetta montana s. l., knowledge of the species diversity and distribution of this group of insects in many European countries has become outdated. This is also true for Poland, where this taxon is rare, and where – of the morphologically cryptic species – only C. cantilatrix has been reported and only in the region of Polish Uplands. From 2021 to 2024, we conducted visual and bioacoustic searching to assess the presence of mountain cicadas in 13 remnant patches of dry grasslands (altogether 40.5 ha) protected as Natura 2000 sites and located between two disjunctive locations of known occurrence of C. cantilatrix. The presence of mountain cicadas has been confirmed at two sites, in Inuletum ensifoliae xerothermic grassland vegetation located on warm and sunny slopes of limestone hills. The two sites found connect the previously known locations of C. cantilatrix in the Polish Uplands. Preserving the remnants of dry grasslands that still exist in the landscape of the studied region seems to be essential for maintaining the functional connectivity of this habitat-specialised insect. Due to the still existing knowledge gaps, it is recommended both to search for new localities in suitable xerothermic biotopes and to verify the presence of mountain cicadas at the few sites of old records. The investigation should include both visual observation and bioacoustic search and analysis. A large number of such results would be necessary for unravelling the taxonomic status and geographical distribution of mountain cicadas both in Poland and Central Europe.